Modeling of Dynamic Links which Characterize Static Properties of Grinding Wheel and Workpiece during Flat Grinding Process. (2019) - Vladetskaya, Ekaterina; Kharchenko, Alexander; Vladetskii, Dmitrii
Abstract: The article considers the results of theoretical and experimental studies of the process of external grinding on the basis of the developed dynamic model. It uses the description of an equivalent dynamic link that converts a standard signal in the form of Gaussian white noise to a random process. For the settings of the forming filter, the results of statistical processing of profilograms of the working surface of the grinding wheel are obtained. The constructed forming filter makes it possible to characterize the statistical properties of the grinding wheel and workpiece. The developed mathematical model of the operation of flat external grinding can be used to assess the quality characteristics of machined parts and systems of automatic process control when solving the problem of intensification of production.